PENGARUH MODAL KERJA TERHADAP PROFITABILITAS DI RUMAH SAKIT HERNA MEDAN - MONTARIS SILAEN; LASMAN EDDY BACHTIAR; RIANTO . (JURNAL ILMIAH KOHESI, 2022)
With good working capital management, it automatically affects the level of profitability of the company. RSU Herna Medan isa company engaged in health. Given the importance of working capital for the company, Herna Medan General Hospitalrequires the effective, efficient and productive use of working capital to increase the company's profits. The formulation of theproblem in this study is "Whether working capital affects profitability in Herna Medan Hospital". From the formulation, thehypothesis in this study is "Working Capital affects profitability in RSU Herna Medan". The population in this study is HernaMedan General Hospital which is located at Jl. Mojopahit No.118A Medan with a 5-year sample consisting of free variablesnamely working capital ratio (X) and profitability-bound variable (Y). To analyze the data used the Simple Linear RegressionMethod with the help of SPSS (Statistical Product and Service Solution) version 18. From the results of research anddiscussion it was concluded that the working capital of Herna Medan Hospital from 2009-2013 experienced an increase anddecrease from period to period and profitability from 2009-2013. The Simple Linear Regression Equation obtained is Y =269.365 + 0.611X. That is, working capital has no effect on the profitability of Herna Medan Hospital. This is evident from thecorrelation value (r) of 0.005. This means that working capital has a very low relationship to profitability in RSU Herna Medanand the amount of Working Capital contribution to profitability of 0.5% and the remaining 95% is influenced by other factorssuch as solvency and liquidity. Advice given to companies and other researchers as information material should thecompany further increase working capital, so that operational activities can run more smoothly again. To get more accurateresults of analysis, other researchers must multiply the sample of research and variables analyzed.